Autonomic arousal to emojis: Electrodermal activity and respiratory sinus arrhythmia analysis - Deeksha Patel; Abhinav Dixit; Om Lata Bhagat (Physiological Reports)
Abstract Emojis have become vital in virtual communication, mimicking facial expressions, and gestures to convey emotions. This study investigates their influence on emotional perception and autonomic responses during non‐face‐to‐face interactions. Hundred healthy participants (50 men, 50 women) aged 18–40 years were recruited. The emotional Stroop task (EST), incorporating emojis with congruent and incongruent emotional words, was used to assess emotional valence. Electrodermal activity (SCL and SCR amplitude) and respiratory sinus arrhythmia (RSA) were measured during task performance. Both SCL and SCR amplitudes were significantly higher in congruent and incongruent blocks compared to the neutral block, indicating increased sympathetic activity. RSA was significantly lower in these blocks, reflecting parasympathetic withdrawal. These findings suggest heightened autonomic responses during emoji‐word EST. Emojis effectively evoke autonomic responses, influencing both sympathetic (EDA) and parasympathetic (RSA) systems. No gender differences were observed in autonomic reactions to emojis. This study highlights the potential of emojis as stimuli for emotion, cognitive and physiological research.